Epidemiology of Burns Injury in dr. Iskak General Hospital Tulungagung: Two Years (2017-2018) Retrospective Study - Ferdianty, Fiera Avrillia; Devina, Santi (Jurnal Plastik Rekonstruksi, 2020)
Introduction: Burn injury is one of the leading causes of morbidity and mortality in low and middle-income countries. Yet in Indonesia, the epidemiology of burn is rarely reported. The study aims to obtain the epidemiological characteristics of burn patients in Dr. Iskak General Hospital. Methods: A retrospective analysis study was used and the medical records of patients with burns admitted at Dr. Iskak General Hospital between January 2017 and December 2018 were collected and analyzed statistically. Results: A total of 80 patients were involved in this study. The most burn victims fell in the adult group (>18 years old), which was 56.3% (n=45). Children were six times more likely to sustain scald burn than adults (OR=6.75I; CI95% 2.47-18.41), meanwhile adults were three times more likely to sustain flame burn than children (OR=3.643; CI95% 1.186-11.190). Most of burn patients (91.25%) were treated surgically. The median of hospital stay was 8 days. Flame burn was the primary etiology for longer hospitalization and there was zero mortality in this study. Conclusion: We found that the adult group was at the highest risk of acquiring burns. Scald was the major cause of burns in children, while flame was the main etiology in the adult group that caused severe burn and prolonged hospitalization.